Equine Infectious Anemia - Case report (Research, Society and Development, 2020)
Equine Infectious Anemia (IEA) is a disease of worldwide distribution and of considerable importance for the horse industry, being one of the eleven notification diseases on the list of the World Organization for Animal Health (OIE). Infectious process that affects horses in general of all ages and races, caused by viruses, transmissible and without cure. Once infected, the animal becomes a source of permanent infection, serving as a reservoir for the virus and capable of transmitting the disease to other animals, which can be asymptomatic. The clinical signs involve high fever (39º to 41ºC), anemia, jaundice, weakness and edema in the limbs and abdomen. The disease is transmitted by bites of tabanids (Tabanus sp.) And barn flies (Stomoxys calcitrans), these being only mechanical vectors, in addition to needles, syringes and utensils contaminated with infected blood, as well as through the transplacental and through semen. contaminated. The diagnosis is made through the Coggins test or Agar Gel Immunodiffusion (AGID) and ELISA, once the disease is confirmed, the Official Service proceeds to sacrifice the positive animal, adopting the other measures for sanitation of the property.